2023
DOI: 10.1101/2023.09.11.557158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Arm Restriction on Dynamic Stability and Upper Body Responses to Lateral Loss of Balance During Walking: An Observational Study

Uri Rosenblum,
Adi Lavi,
Arielle Fischer
et al.

Abstract: BackgroundWhen losing balance, arm movements serve as a mechanical aid to regain stability. However, it remains unclear how arm movements contribute to dynamic stability during recovery from a lateral loss of balance while walking. Our objectives were to 1) quantify the effect of arm restriction on gait stability and upper body velocities; 2) test the association between gait stability and upper body velocities; 3) analyze upper body kinematics and strategies in response to lateral surface translations under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Having majority of the weight of the body rapidly rotating towards the left or the right would be difficult to control as it carries most of the mass of the body. One study showed that head and trunk velocities were significantly greater in the frontal plane compared to the sagittal plane during a walking treadmill slip [35]. This issue of frontal plane loss of balance becomes more troublesome when applying this concept to older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Having majority of the weight of the body rapidly rotating towards the left or the right would be difficult to control as it carries most of the mass of the body. One study showed that head and trunk velocities were significantly greater in the frontal plane compared to the sagittal plane during a walking treadmill slip [35]. This issue of frontal plane loss of balance becomes more troublesome when applying this concept to older adults.…”
Section: Discussionmentioning
confidence: 99%